Detection of Biogenic Amines in Indian Fish and Fishery Products Consumed in Southeast Coast Region of India. Issue 1 (2nd January 2021) - Arulkumar, Abimannan; Paramasivam, Sadayan; Rameshthangam, Palanivel; Paramithiotis, Spiros
ABSTRACT: The aim of the present study was to assess the occurrence of seven biogenic amines (cadaverine, histamine, putrescine, tryptamine, tyramine, spermidine, and spermine) in 13 fresh fish, three crustaceans, and three cephalopod species, as well as six cured and dried fish products commonly consumed in the southeast coast region of India. The biogenic amines were analyzed by high performance liquid chromatography with a dansyl chloride derivatization. In the majority of the cases, the biogenic amine content was within the limits set at both national and international levels. The only exceptions were the histamine content of fresh Silago sihama, Lutjanus bohar, and L. johnii, cured and dried Rastrelliger kanagurta and the tyramine content of cured and dried Penaeus indicus . In these cases, lack of proper temperature handling was indicated, which highlights the importance of establishing and implementing proper handling procedures to ensure fish and fishery product safety for human consumption. Graphical Abstract: